Indonesian Foreign Policy in the Case of Illegal Fishing of Vietnamese Fishermen in the Natuna Islands on the Border of Indonesia and Vietnam in 2014-2021 - Agria Ningrum, Syeti; Elyta, Elyta; Nuzulian, Ully (PT. Riset Press International, 2024)
Illegal fishing is part of a transnational crime that has an impact on Indonesia's losses because it can cause a reduction in the scale of production and damage to natural ecosystems. Currently, Indonesia is one of the potential zones in the 14 fishing ground zones in the world. Issues related to illegal fishing are not new cases on Indonesia's borders. One of them is that the border waters between Indonesia and Vietnam often involve transnational illegal fishing crimes. In explaining this case, the author uses the concept of Transnational Organized Crime (TOC) and Foreign Policy theory which aims to explain and describe Indonesia's foreign policy. This research uses a qualitative method with a qualitative descriptive approach, where the author will provide a general description of the problem and then draw specific conclusions. UNCLOS 1982 is Indonesia's long-term goal to address illegal fishing cases. Law no. 5 of 1983 concerning the Indonesian Exclusive Economic Zone (ZEEI) also regulates UNCLOS violations regarding illegal hunting. This law regulates fish resource utilization activities in the Exclusive Economic Zone. In Foreign Policy, Indonesia also identifies the cooperative relations agreement between Indonesia and Vietnam, as well as Presidential Decree number 16 of 2017 concerning Indonesian maritime policy. However, Indonesian policies have not had a significant impact in reducing the number of illegal fishing cases in Indonesia.